Unroofing the Klamaths - Blame it on Siletzia? - Piotraschke, R.; Cashman, S.; Furlong, K.; Kamp, P.; Danisik, Martin; Xu, G. (Geological Society of America, 2015)
The Klamath Mountains province of northwestern California–southwestern Oregon is an anomalous element in the Cascadia margin; these mountains have the highest average topography, the oldest rocks, and the only identified example of late Cenozoic detachment faulting in the coastal mountains of the Cascadia forearc. Low-temperature thermochronology (apatite fission-track, apatite [U-Th]/He) analyses from the central and southern Klamath Mountains province record two distinct exhumation events—a Cretaceous–Paleocene regional cooling and a southward-migrating locus of rapid cooling/exhumation in the middle Tertiary. This younger event is localized within the geographic extent of the La Grange fault. We infer that this pattern reflects two distinct processes of exhumation: regional surface erosion (older) and migrating localized tectonic exhumation (younger). At the southern limit of this region of rapid cooling, slickenside striations on the exposed La Grange fault surface record southward displacement of the upper plate along a shallowly dipping (~20°) detachment surface. Thermochronologic data constrain average dip of the fault to a few degrees, upper-plate thickness to <~6–8 km, and fault slip rate to <2 mm/yr for a duration of 30 m.y. (ca. 45 Ma to 15 Ma). The fault dip is unusually low compared to that of typical detachment faults; the duration of this extensional event is unusually long compared to other detachment faults; the north-south (margin-parallel) slip direction is roughly perpendicular to that of other Klamath Mountains province faults; and the Eocene to early Miocene timing of extensional faulting does not correlate with recognized tectonic events in northern California. Mid-Tertiary tectonic events in the Oregon Coast Ranges provide a context for understanding the unusual mid-Tertiary tectonism in the Klamath Mountains province. Immediately north of the Klamath Mountains province, early Eocene accretion of a large early Cenozoic igneous province, the Siletz terrane, initiated a westward jump of active subduction. Accretion was followed by late Eocene margin-parallel extension in the Oregon Coast Ranges, recorded by formation of a regional dike swarm. Both the timing of tectonic exhumation and the direction of extension on the La Grange detachment fault suggest that mid-Tertiary tectonism in the southern Klamath Mountains province was likely driven by plate tectonics associated with the accretion of Siletzia and the reestablishment of subduction outboard of the accreted terrane.